PENGGUNAAN KOTAK MISTERI (MYSTERY BOX) SEBAGAI MEDIA PRESENTASI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA - Nurmina; Arief Muhsin; Andy Asri Jumiaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking skill is a crucial ability for students to master in English language learning; however, many students still struggle to express their ideas due to limitations in vocabulary, pronunciation, grammar, fluency, and accuracy. This study aims to determine the improvement in students' speaking skills through the use of the Mystery Box Presentation Game. The study employed Classroom Action Research (CAR) methodology conducted over two cycles, with each cycle comprising planning, action implementation, observation, and reflection stages. The subjects were 32 students from class X.4 at MAN 1 Makassar during the 2025/2026 academic year. Research instruments included speaking tests and observation sheets. Data were analyzed using descriptive statistics—calculating mean scores, score classifications, and percentage improvements—while observational data were analyzed descriptively. The results indicate that the Mystery Box Presentation Game successfully improved students' speaking skills. This improvement was evident in the rise of students' mean scores across cycles and the shift in score classifications from the "low" category to "Good" and "Very Good." Furthermore, all aspects of speaking skills—pronunciation, fluency, accuracy, grammar, and vocabulary—showed improvement. Observations also revealed that students became more active, confident, and motivated to participate in classroom speaking activities. Thus, it can be concluded that the Mystery Box Presentation Game is an effective teaching strategy for enhancing students' speaking skills.